2006
DOI: 10.1111/j.1365-2982.2006.00853.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the effects of short‐chain fatty acids on intestinal motility in vitro and GPR43 receptor activation

Abstract: The G protein-coupled receptors, GPR41 and GPR43, are activated by short-chain fatty acids (SCFAs), with distinct rank order potencies. This study investigated the possibility that SCFAs modulate intestinal motility via these receptors. Luminal SCFA concentrations within the rat intestine were greatest in the caecum (c. 115 mmol L(-1)) and proximal colon. Using similar concentrations (0.1-100 mmol L(-1)), SCFAs were found to inhibit electrically evoked, neuronally mediated contractions of rat distal colon, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
1
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(125 citation statements)
references
References 37 publications
6
112
1
6
Order By: Relevance
“…Gene expression levels of both GPR41 and GPR43 in the stomach and small intestine are comparatively lower than other tissues including spleen, bone marrow and other tissues (1,11). On the other hand, quantitative real-time PCR revealed that GPR43 gene expression in the large intestine was higher than in other regions of the GI tract (5). Furthermore, we recently reported the presence of GPR43 in the rat terminal ileum and colon (8) and human colon as well as its gene and protein expression patterns (9).…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Gene expression levels of both GPR41 and GPR43 in the stomach and small intestine are comparatively lower than other tissues including spleen, bone marrow and other tissues (1,11). On the other hand, quantitative real-time PCR revealed that GPR43 gene expression in the large intestine was higher than in other regions of the GI tract (5). Furthermore, we recently reported the presence of GPR43 in the rat terminal ileum and colon (8) and human colon as well as its gene and protein expression patterns (9).…”
Section: Methodsmentioning
confidence: 94%
“…The rabbits were bled from the marginal ear vein, ten days after each immunization. After six immunizations, one of the three rabbits revealed a high titer antiserum (RY1494) against human GPR41 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), and was used for the present study.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanisms for this are thought to be related to alterations in the intestinal microflora and production of short chain fatty acids SCFA, which biological and clinical properties have been extensively investigated [22,23]. SCFA stimulate the motility of the intestine probably through colonic motility by stimulating mucosal receptors connected to enteric and vagal nerves [56], colonic smooth muscle [57], and releasing gastrointestinal regulatory peptides that modulate intestinal motility such as polypeptide YY [58]. The motility of the GIT is important for absorption, transport, and clearance.…”
Section: Chronic Constipationmentioning
confidence: 99%
“…Within the human colon, concentrations of acetate, propionate and butyrate were reported to be in the range of 20-43 mmol/L, 6-13 mmol/L and 6-15 mmol/L, respectively [21] . GPR43 has been reported to be expressed in human, mouse and rat colons [22][23][24] . Induction of antiinflammatory activities by SCFAs in the colon may contribute to the bacterial evasion of the immune system [25] .…”
Section: Introductionmentioning
confidence: 99%